The interactions between inflammation and coagulation - Esmon, Charles T. (British journal of haematology, 2005)
Summary Inflammation initiates clotting, decreases the activity of natural anticoagulant mechanisms and impairs the fibrinolytic system. Inflammatory cytokines are the major mediators involved in coagulation activation. The natural anticoagulants function to dampen elevation of cytokine levels. Furthermore, components of the natural anticoagulant cascades, like thrombomodulin, minimise endothelial cell dysfunction by rendering the cells less responsive to inflammatory mediators, facilitate the neutralisation of some inflammatory mediators and decrease loss of endothelial barrier function. Hence, downregulation of anticoagulant pathways not only promotes thrombosis but also amplifies the inflammatory process. When the inflammation–coagulation interactions overwhelm the natural defence systems, catastrophic events occur, such as manifested in severe sepsis or inflammatory bowel disease.